The Longitudinal Measurement of Reasoning Abilities in Students With Special Educational Needs - Gnambs, Timo; Nusser, Lena (Frontiers in Psychology, 2019)
Students with special educational needs in the area of learning (SEN-L) have learning disabilities that can lead to academic difficulties in regular schools. In Germany, these students are frequently enrolled in special schools providing specific training and support for these students. Because of their cognitive difficulties, it is unclear whether standard achievement tests that are typically administered in educational large-scale assessments are suitable of students with SEN-L. The present study evaluated the psychometric properties of a short screening instrument for reasoning abilities that was administered as part of a longitudinal large-scale assessment to German students from special schools (N = 324) and basic secondary schools (N = 338) twice within six years. Item response modeling demonstrated an essentially unidimensional scale for both school types. Few items exhibited systematic differential item functioning (DIF) between students with and without SEN-L, allowing for valid cross-group comparisons. However, change analyses across the two time points needed to account for longitudinal DIF among students with SEN-L. Overall, the cognitive test allowed for a valid measurement of reasoning abilities in students with SEN-L and comparative analyses regarding students without SEN-L. These results demonstrate the feasibility of incorporating students with SEN-L into educational large-scale assessments.